Interaction of obesity and atrial fibrillation: an overview of pathophysiology and clinical management. (4th March 2019) - Pouwels, Sjaak; Topal, Besir; Knook, Mireille T.; Celik, Alper; Sundbom, Magnus; Ribeiro, Rui; Parmar, Chetan; Ugale, Surendra
ABSTRACT: Introduction : Obesity, defined as a Body Mass Index (BMI) of ≥30 kg/m2, is the most common chronic metabolic disease worldwide and its prevalence has been strongly increasing. Obesity is associated with various diseases such as cardiovascular disease, type 2 diabetes, and hypertension. Regarding heart rhythm disorders, obesity is associated with an increase in atrial fibrillation (AF), the most common arrhythmia in clinical practice. AF is associated with increased cardiovascular morbidity and mortality. Obesity, a novel risk factor, is responsible for a 50%-increased incidence of AF. Areas covered : We will briefly discuss the obesity paradox and its mechanisms regarding cardiac and hemodynamic function changes. In the first main part of this review, we will be discussing risk assessment studies, pathophysiology, genetic predisposition, epicardial adipose tissue, and ventricular adaptation in relation to obesity and development of AF. In the second part, we will discuss treatment strategies like conservative management and the effect of bariatric and metabolic surgery. Expert opinion : Cardiac arrhythmias, in particular, AF, in patients with obesity comprise complex pathophysiological mechanisms that remain poorly understood. In recent literature, there has been increased interest in the role of epicardial adipose tissue and structural remodeling in obese hearts.